IFDC: Improving the use of fertilizers in Third World countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The use of fertilizers in many Third World countries has increased greatly during the last decade. About 40% of the world's nitrogen fertilizer and 30% of its phosphate fertilizer now go to tropical or sub-tropical regions. But not all fertilizers...